On belonging of characteristic functions of probability laws to a convergence class - Kulyavetc, Lubov; Mulyava, Oksana; Sheremeta, Miroslav (My University, 2013)
It is investigated the condition on a probability law, under which its characteristic function belongs to a convergence class. Досліджено умову на ймовірнісний закон відповідно до якого характеристична функція належить до класу збіжності.
Keywords: кафедра вищої математики імені проф. Можара В. І.; імовірнісний закон; характеристична функція; клас збіжності; probability law; characteristic function; convergence class